2002
DOI: 10.1007/s10198-002-0125-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in dual-diagnosis and nonaddicted schizophrenics: are there differences?

Abstract: Analysis of 447 schizophrenic inpatients found a lifetime prevalence for substance use of 42.9% (3-month prevalence 29%). While the overall differences were small between schizophrenics using (dual diagnosis) and those not using substances, dual-diagnosis patients in general reported more positive symptoms, especially more intense hallucinations. These differences were observed in patients with current (3-month) substance use on admission but not on discharge, possibly as a result of substance use. The most ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
2
5
0
1
Order By: Relevance
“…This figure falls into the mid-range of previous findings in the UK where widely varying estimates ranging from two to 68% in MHS and four to 83% in DAS were reported [22-23, 31, 36, 59-60]. Similarly, our findings fit well with recent non-UK studies, which reported prevalence rates ranging from six to 78% in the US [61][62][63], 34 to 51% in Norway [7], 14 to 45% in Canada [6], 29% to 43% in Germany [64] and 27 to 49% in Spain [65] across different treatment settings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This figure falls into the mid-range of previous findings in the UK where widely varying estimates ranging from two to 68% in MHS and four to 83% in DAS were reported [22-23, 31, 36, 59-60]. Similarly, our findings fit well with recent non-UK studies, which reported prevalence rates ranging from six to 78% in the US [61][62][63], 34 to 51% in Norway [7], 14 to 45% in Canada [6], 29% to 43% in Germany [64] and 27 to 49% in Spain [65] across different treatment settings.…”
Section: Discussionsupporting
confidence: 92%
“…This figure falls into the mid-range of previous findings in England, where widely varying estimates ranging from 2% to 68% in MHS and 4% to 83% in DAS were reported [22,23,31,36,59,60]. Similarly, our findings fit well with recent non-UK studies, which reported prevalence rates with a range of 6-78% in the United States [61][62][63], 34-51% in Norway [7], 14-45% in Canada [6], 29-43% in Germany [64] and 27-49% in Spain [65] across different treatment settings. The obtained prevalence rates might be underestimates, as our findings suggest that many services may fail to identify DD because no comprehensive assessments are undertaken with new clients.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, visual deterioration has been associated with the risk for criminal behavior (Bachara and Zaba, 1978; Zinkus and Gottlieb, 1978; Lane, 1980; McKay and Brumback, 1980; Broder et al, 1981; Clack, 1990), one of the strongest indicators of a severe course (Steinert, 1998; Nedopil, 2007; Hutton et al, 2012), outcome (Leygraf, 1988; Haller et al, 2001; Soyka and Morhart-Klute, 2002; Soyka et al, 2002; Fazel et al, 2009; Nitschke et al, 2011; Kooyman et al, 2012), and relapse (Soyka et al, 2004; Witt et al, 2013) in schizophrenia. Specifically, it was argued that in very young children and juveniles, perceptual deficits lead to a higher rate of learning disabilities, specifically reading problems.…”
Section: The Therapeutic Perspective On Schizophreniamentioning
confidence: 99%
“…This situation may deprive patients of the opportunity to receive appropriate treatment, with possibly severe consequences for the patients' psychiatric morbidity [5,6,7,8]. This study shows that AUDIT and DUDIT may provide precise information about the drug use of emergency psychiatric patients, and in view of the simplicity of the instruments, routine implementation may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…In groups of psychiatric inpatients, prevalence rates of SUD as high as 50% are commonly reported [2,3,4]. The presence of SUD among psychiatric patients is associated with more severe symptoms, higher admission rates, and increased risk of violence and suicide [5,6,7,8]. Many studies indicate that treatment of SUD among psychiatric patients is associated with better drug-related, psychiatric and psychosocial outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%